Analisis Penguatan Pendidikan Karakter (PPK) dalam Pembelajaran IPS Pada Materi Ragam Pekerjaan - Nurazijah, Mira; Rizkya Rudianti, Sandra; Nurbayanti, Saskia; Yanti, Syarifah Dwi; Rustini, Tin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
In the world of education, the instillation of character values ​​is realized through educational policies to strengthen character in students known as Strengthening Character Education (PPK). One effort in implementing Strengthening Character Education (PPK) can be done through learning content implemented in schools. This study aims to gain an understanding of Strengthening Character Education (PPK) through IPS content contained in the material of various jobs in grade IV of Elementary School. The method used in this study is a literature review, with data analysis techniques through the stages of collecting, reducing, and drawing conclusions from various literature obtained from various sources. The results of the analysis found that Strengthening Character Education (PPK) through IPS content in the material of various jobs in grade IV of elementary school, emphasizes more on the values ​​of mutual cooperation and integrity. Social studies material for various jobs not only provides an understanding of the importance of dedication and responsibility to students, but also builds students' personal character who is independent, able to work together, and has high integrity.